Diagnosis and management of melanoma with regional lymph node metastases: a population‐based study in France. (30th July 2012) - Lévy‐Sitbon, C.; Barbe, C.; Granel‐Brocard, F.; Lipsker, D.; Aubin, F.; Dalac, S.; Truchetet, F.; Michel, C.; Mitschler, A.; Arnoult, G.; Le Clainche, A.; Dalle, S.; et al.
Abstract: Background Stage III melanoma represents a borderline situation regarding the potential curability of this potentially aggressive cancer and consequently, regional lymph node metastases (RLNM) are a major challenge for melanoma management. Objective To describe the management of melanoma with RLNM as practised in France in 2008 and compare results with previous data from 2004, considering that new French recommendations were published in 2005. Methods Retrospective population‐based study in five regions of France totalling 8.3 million inhabitants, targeting all incident cases of RLNM diagnosed in 2008. Questionnaires were mailed to physicians to identify cases and collect data, with verification by cancer registries for cases diagnosed concomitantly with the primary tumour using sentinel lymph node biopsies (SLNB). Results Data were collected for 101 patients in 2008, and compared to 89 cases treated in 2004. Palpation by a dermatologist was the most common circumstance of diagnosis of RLNM in 2008 (36%), followed by SLNB (29%), self‐palpation by the patient (16%) and lymph node ultrasonography (6%), without significant modification from 2004. After lymphadenectomy an adjuvant therapy was proposed in 62% of cases, mainly consisting in high‐dose interferon (HD‐IFN) (80%). Overall, HD‐IFN was proposed in 49% of cases, but effectively started in only 40% of cases after being proposed, and prematurely withdrawn in 28%, showing major changes as compared with 2004 (33%, 77% and 67%, respectively, P < 0.05). Adjuvant chemotherapy was not proposed to any patients in 2008, compared to 29% in 2004. Surveillance procedures included medical imaging less often in 2008 (76%) than in 2004 (92%) ( P = 0.004), but more often included FDG‐PET (23% vs. 12%, P = 0.09). Conclusion Overall, actual practice was in accordance with French recommendations. The main developments from 2004 to 2008 were the disappearance of adjuvant chemotherapies and a more accurate selection of patients for adjuvant interferon.